Public-Private Partnerships for Stimulating the Eco-Efficiency and Environmental Responsability of SMEs - Bogdana NEAMŢU (Transylvanian Review of Administrative Sciences, 2011)
This paper investigates the trend of greening the SMEs sector by means of creating publicprivate partnerships. There are two main theoretical concepts used to frame the debate – social corporate responsibility and eco-efficiency. The paper describes and analyzes one possible tool local governments have in order to encourage SMEs to become more efficient from an environmental standpoint – the Ecoprofit-type approach. Ecoprofit is a program implemented in Austria and then extended to other countries in which local governments offer training and certificates to SMEs who want to become more eco-efficient. In the empirical research we tested: a) the perceptions and attitudes of SMEs with regard to the greening of their operations and products/ services; and b) whether Romanian SMEs would be interested in taking part in such a program. The conclusion is that SMEs perceive environmental management as a burden and tend to comply only with the mandatory requirements of the law